1996
DOI: 10.1210/endo.137.2.8593800
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variation in resting levels of corticosterone is not mediated by variation in adrenal responsiveness to adrenocorticotropin but involves splanchnic nerve integrity.

Abstract: To study possible mechanisms controlling diurnal changes in corticosterone (CORT) levels, we tested the CORT responses to ACTH in the morning (AM) and evening (PM) in male Wistar and Sprague-Dawley rats. Rat ACTH-(1-39) or human ACTH-(1-24) (3.75-15 ng/rat) was given as an iv bolus or an intraarterial infusion to (un)anesthetized rats treated with dexamethasone (0.1-0.5 mg/kg, 2-6 h before ACTH). In all conditions studied, no AM/PM differences in CORT responses were found when ACTH was given in vehicle (pH 4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 44 publications
2
30
1
Order By: Relevance
“…Jasper and Engeland (1994) showed that denervation of the adrenal gland by removal of its sympathetic innervation resulted in increased secretory activity of the adrenal cortex during the daytime, thus supporting our suggestion for an important daytime inhibition of corticosterone release via the neural input to the adrenal gland. Recently, Dijkstra et al (1996) also showed that the sympathetic innervation of the adrenal gland contributes to the diurnal variation in resting plasma corticosterone levels. However, evidence also was provided that this is not attributable to a change in the adrenal responsiveness to ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…Jasper and Engeland (1994) showed that denervation of the adrenal gland by removal of its sympathetic innervation resulted in increased secretory activity of the adrenal cortex during the daytime, thus supporting our suggestion for an important daytime inhibition of corticosterone release via the neural input to the adrenal gland. Recently, Dijkstra et al (1996) also showed that the sympathetic innervation of the adrenal gland contributes to the diurnal variation in resting plasma corticosterone levels. However, evidence also was provided that this is not attributable to a change in the adrenal responsiveness to ACTH.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to ACTH challenge, blood was sampled at 0800 hours to establish a baseline level of CORT. Mice were then given an injection of dexamethasone (0.05 mg/kg) in order to limit endogenous ACTH release (Dijkstra et al, 1996;Han et al, 1998;Michopoulos et al, 2012;Otsuka et al, 2012). This dose of dexamethasone was chosen as it exhibited equivalent CORT suppression in both groups following peripheral administration in Experiment 2.…”
Section: Acth Challengementioning
confidence: 99%
“…However, there is still conflicting evidence on the issue of the daily alterations in adrenal responsiveness and accompanying HPA axis reactivity. For instance, it has been argued that the diurnal changes in GC require splanchnic nerve integrity but are not mediated by differential responsiveness to ACTH (12). It has also been shown that the response to a mild stress failed to support increased HPA axis reactivity during the active period (13).…”
Section: G Lucocorticoid [Gc; Corticosterone (Cs) In Rodents Andmentioning
confidence: 99%